Lightering passengers from steamship VICTORIA, probably Nome, July 2, 1907 - Nowell, Frank H., 1864-1950 (1907)
Caption on image: Lightering Passengers from S.S. Victoria, July 2nd 1907. F.H. Nowell, 5433 1/2 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number